Prosocial behavior increases perceptions of meaning in life. Issue 4 (4th July 2017) - Klein, Nadav
Abstract: Finding meaning in life is a fundamental personal need, and motivating prosocial behavior is a fundamental societal need. The present research tests whether the two are connected – whether helping other people can increase helpers' perceptions of meaning in life. Evidence from a nationally representative data-set and two experiments support this hypothesis. Participants who engaged in prosocial behaviors – volunteering and spending money to benefit others – reported experiencing greater meaning in their lives (Studies 1–3). Study 3 also identifies increased self-worth as the mechanism – participants who spent money to benefit other people felt higher personal worth and self-esteem, and this mediated the effect of prosocial behavior on meaningfulness. The present results join other findings in suggesting that the incentives for helping others do not necessarily depend on the prospect of others' reciprocity. Prosocial behavior can be incentivized through the psychological benefits it creates for prosocial actors.